2020
DOI: 10.1177/0020294020902785
|View full text |Cite
|
Sign up to set email alerts
|

Proposed particle swarm optimization technique for the wind turbine control system

Abstract: Wind energy is a useful and reliable energy source. Wind turbines are attracting attention with the dependency of the world on clean energy. The turbulent nature of wind profiles along with uncertainty in the modeling of wind turbines makes them more challenging for prolific power extraction. The pitch control angle is used for the effective operation of wind turbines at the above-nominal wind speed. To extract stable power as well as to keep wind turbines in a safe operating region, the pitch controller shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The parameters of the simulated PMGS-based WT system and PSO algorithm are given in the Tables 1 and 2 (Asgharnia et al, 2018; Dorrah et al, 2012; Iqbal et al, 2020).…”
Section: Results Of Calculationmentioning
confidence: 99%
“…The parameters of the simulated PMGS-based WT system and PSO algorithm are given in the Tables 1 and 2 (Asgharnia et al, 2018; Dorrah et al, 2012; Iqbal et al, 2020).…”
Section: Results Of Calculationmentioning
confidence: 99%
“…Particle swarm optimization (PSO) is a population-based, stochastic evolutionary computer technique for problem-solving [54]. It is a type of swarm intelligence, based on socio-psychological concepts, that gives insights into social behavior while also contributing to technical applications.…”
Section: Pso Overviewmentioning
confidence: 99%
“…The use of these smart algorithms leads to a significant improvement in the efficiency of the systems. In Iqbal et al, 38 the PSO algorithm is used to calculate the PI controller parameters of a wind turbine control system based on DFIG to improve the current quality. Simulation was used to implement this intelligent control with a comparison of the results with the traditional control that depends on the PI, where the results showed that the use of the PSO algorithm leads to a significant improvement in the characteristics of the system compared to the DPC.…”
Section: Introductionmentioning
confidence: 99%